Interaction between coaches and athletes in African nations during the lockdown period of COVID-19 - Luguterah, A. W.; Abonyi, U.; Yeboah, R.; Kubayi, A. (International Sport Coaching Journal, 2023)
The lockdown period of the COVID-19 pandemic has created several innovative methods of interaction at workplaces and, more importantly, within the sports industry. The COVID-19 pandemic has affected the usual training procedures and further challenged coaches and athletes to find ways of interaction. The researchers combined both qualitative and quantitative approaches and descriptive statistics in this article. This article attempts to find out the means, media, experiences, and source of interaction between coaches and athletes in five African countries during the COVID-19 lockdown period. Data were gathered from 127 coaches and 212 athletes from five African countries. The article reveals that coaches and athletes made use of phone calls, emails, text messages, and internet videos to interact during the lockdown period. The athletes benefited from the interactions, and the coaches achieved their coaching goals. The finding of this study, apart from triggering research on the use of technology in sports coaching in Africa, further creates a new path of distant coaching in Africa.